Social determinants related to food insecurity among nutrition students at a Mexican university - Sánchez, Susana; Orozco González, Claudia Nelly; González Fajardo, Krystal Dennicé (Horizonte Sanitario, 2025)
Objective: Identify food insecurity (FI) in university students of nutrition, as well as its association with social determinants of health (SDH) and with being beneficiary of social programs. Materials and methods: A transversal study with a sample of 213 university students of nutrition, 17 to 39 years of age. The dependent variable was food insecurity, and the independent variables were age, sex, parents’ level of education, socioeconomic level, ethnicity, housing, student employment, social security and diversity of diet. Prevalences, bivariate associations, and models of multinomial logistic regression (odds ratio [OR] and confidence interval at 95% [CI 95%]) were calculated. Results: Of the sample of university students, 47.9% were classified with FI. The strongest predictors of slight food insecurity were social security (OR: 0.40; CI95%: 0.19-0.82; p=0.013), home ownership (OR: 0.41; CI95%: 0.17-0.95; p= 0.037), and high socioeconomic level (OR: 0.24; CI95%: 0.07-0.84; p= 0.025). In the case of moderate and severe food insecurity, the determining protector was the father’s fixed salary (OR: 0.29; CI95%: 0.11-0.74; p=0.009), and the mean diversity of the diet was a risk factor (OR: 2.74; CI95%: 1.06-7.13; p=0.038). Conclusion: Food insecurity is highly prevalent in this population of university students. Some social determinants of health influenced the increase or decrease in the probability of FI. Social programs were not related to FI. Key words: Social determinants of health; Food insecurity; Social programs; Health sciences students.